THE INFLUENCE OF TAPING IN ANKLE´S RANGE OF MOTION OF VOLLEYBALL PLAYERS (Fiep Bulletin - online, 2013)
Objectives: The aim of this study is to determine if the application of bandage ankle through tape (taping) can promote isolation restriction of movement of ankle inversion, and if this keeps up after 60 seconds of multiple jumps. Methods: A sample of athletes in women's volleyball (n = 9; 15.88 ± 1.53 years; 176 ± 0.08 cm, 69.4 ± 11.5 kg). The evaluations took place in two separate stages, defined by lottery, with an interval of one month: a) experimental evaluation (banded), which became goniometric evaluation for the movements of inversion, dorsiflexion and plantarflexion. Following applied dominant ankle taping and redid the measurements of goniometry. Then we applied the 60 seconds (s) jumping test and remade itself goniometric assessments, b) assessment control (no bandage) became goniometry (inversion, dorsiflexion and plantarflexion). Then we applied the 60s jump test was remade itself measures goniometry. Results: The taping restricted significantly the movements of inversion and plantarflexion and these remained restricted after the jumps. And increased range of motion of dorsiflexion after jumping test. Dorsi / Mauchly = 0.681, p = 0.261, F (2, 16) = 7.03, p = 0.01. Planti / Mauchly = 0.449, p = 0.061, F (2, 16) = 27.39, p
Keywords: Physical therapy modalities; volleyball; arthrometry articulate